Virome in Fecal Samples From Wild Giant Pandas (Ailuropoda Melanoleuca) - Ning, Songyi; Lu, Xiang; Zhao, Min; Wang, Xiaochun; Yang, Shixing; Shen, Quan; Wang, Hao; Zhang, Wen (Frontiers in Veterinary Science, 2021)
The giant panda (Ailuropoda melanoleuca) is one of the most endangered mammals in the world, anthropogenic habitat loss and poaching still threaten the survival of wild pandas. Viral infection have become one of the potential threats to the health of these animals, but the available information related to these infections is still limited. In order to detect possible vertebrate viruses, the virome in the fecal samples of seven wild giant pandas from Qinling Mountains were investigated by using the method of viral metagenomics. From the fecal virome of wild giant pandas, we determined six nearly complete genomes belonging to the order Picornavirales, two of which may be qualified as novel virus family or genus. In addition, four complete genomes belonging to the Genomoviridae family were also fully characterized. This virological investigation has increased our understanding of the gut viral community in giant pandas. Whether these viruses detected in fecal samples can really infect giant panda needs further research.